Formation of Logistic Chain of Gas Supply Within the Context of Implementation of the Law «About the Natural Gas Market» - Полянська, А. С. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2018)
The advisability and preconditions of industry enterprises’ integration in the logistic chain and logistics network are investigated. It is grounded that the solution of this problem in the gas supply system depends on modern approaches to the development of the supply chain in the natural gas market in Ukraine, based on consideration of the following criteria: forming of a competitive environment through the integration of all stakeholders in the chain of energy resources supply; organization of all players in the logistics chain so that the added value at each stage of the movement of material resources was created, and the display of which can be seen by the quality of services and established products. It is summarized that the implementation of oil and gas companies’ strategic objectives is possible by using of their organizational capacity through the use of network structures and their interaction with supply chains. Attention is paid to the fact that the integration of activities within the logistics chain requires consideration of industry enterprises’ readiness to integrate adaptation based on international standards activities in the oil and gas sector, European quality standards. It is proved that an important background for the integration of specialized enterprises in to the logistics supply chain is the achievement of an adequate level of efficiency, which will enable them to compete within the existing competitive logistic chains both on the national and on the international levels.